Pendampingan Program Bantuan Zakat Rumah Tidak Layak Huni (RTLH) bagi Dhuafa Sebatang Kara di Kabupaten Bondowoso - Mohammad Firmansyah; Kamelia; Hoiriyah; Humayrotul Hasanah (Transformative Service Journal, 2026)
This community service program aims to provide assistance in the distribution of zakat funds for beneficiaries of Uninhabitable Houses (RTLH) among underprivileged individuals living alone in Bondowoso Regency. The method employed was direct field assistance through observation, interviews, and active participation in the zakat distribution process. The service team assisted 20 underprivileged individuals who had no family support and were living in uninhabitable housing conditions. Each beneficiary received monthly cash assistance of IDR 600,000 to meet their daily living needs. The results indicate that the zakat assistance program was well-targeted and provided tangible benefits in improving the welfare of the beneficiaries. The direct involvement of the service team in the assistance and distribution process also enabled a comprehensive understanding of the social and economic conditions and the actual needs of the beneficiaries. This program is expected to serve as a sustainable zakat assistance model and to be expanded more broadly as part of poverty alleviation efforts.